الكناية في الحديث والأثر عن فضل العلم في كتاب آداب العالم والمتعلم: دراسة بلاغية: Metonymy in Hadith and Athar on Knowledge’s Virtue in Adab Al-Alim Wal-Mutaallim: A Rhetorical Study - Nisa Halimatussa'adah; Mohamad Anang Firdaus; M. Rizki Syahrul Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This research issnvestigates the application of al-Kinayah (implicit/metaphorical expression) in the Hadiths and Athars within